2016
DOI: 10.1126/sciadv.1500882
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of chromosome architecture in replicative cellular senescence

Abstract: Senescent cells acquire a unique chromosome architecture characterized by a genome-wide shrinkage of chromosome arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
138
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(155 citation statements)
references
References 67 publications
16
138
1
Order By: Relevance
“…Recently, analysis of 3D chromosomal architecture using combined biochemical, cytological, and computational techniques has revealed significant decreases in volume, and increases in chromosome compaction during cellular senescence [227]. This unique senescent chromosomal signature is attributed to an increase in short-range chromatin contacts and genome-wide contraction of chromosome arms.…”
Section: Redox Control Of Sasp and Age-related Pathologiesmentioning
confidence: 99%
“…Recently, analysis of 3D chromosomal architecture using combined biochemical, cytological, and computational techniques has revealed significant decreases in volume, and increases in chromosome compaction during cellular senescence [227]. This unique senescent chromosomal signature is attributed to an increase in short-range chromatin contacts and genome-wide contraction of chromosome arms.…”
Section: Redox Control Of Sasp and Age-related Pathologiesmentioning
confidence: 99%
“…Changes in chromosome organization identified in RS cells by Hi-C were intermediate between the OIS and HGPS cells [63]. Genome-wide, RS cells displayed a global increase in short-range contacts.…”
Section: Senescent Cells Display Extensive Changes In Chromatin Strucmentioning
confidence: 99%
“…In contrast to HGPS, which showed a dramatic loss of compartmentalization, the overall 3D organization of chromosomes was maintained in RS cells. By conducting a variety of complementary experiments including chromosome painting and 3D DNA FISH, it was concluded that the increased short-range contacts could be attributed to a decrease in the volume occupied by chromosome arms (Figure 1) [63]. This was in stark contrast to the behavior of centromeres, which showed significant decondensation as described below.…”
Section: Senescent Cells Display Extensive Changes In Chromatin Strucmentioning
confidence: 99%
“…Repositioning of the heterochromatin regions from the periphery to the nuclear center generates novel genetic interaction domains, largely known as senescence-associated heterochromatic foci (SAHF), which are usually associated with repressive histone marks, such as histone 3 lysine 9 trimethylation (H3K9me3) [10]. A whole-genome chromosome conformation capture (Hi-C) analysis in human senescent fibroblasts has unraveled that certain topologically associated domains (TAD) are relocated acquiring novel short-range interactions while losing long-range interactions within chromosomes [15]. Another Hi-C study of senescent fibroblasts has shown that the local genetic interactions within SAHF domains are weakened [14].…”
Section: Nuclear Reorganization: Chromatin Remodeling and The Nuclearmentioning
confidence: 99%